Effect of Slaughtering Age on Chemical Composition of Goat Meat - Arain, Mohammad Asif; Khaskheli, M.; Rajput, I.R.; Faraz, S.; Rao, S.; Umer, M.; Devrajani, K. (Pakistan Journal of Nutrition, 2010)
The research consist of chemical analysis of the goat meat to investigate the relationship between goat meat in different age groups, group A (<7 m), group B (8-10 m) and group C (>11 m). Chemical characteristics of goat meat in respect of moisture, protein, fat and ash contents were determined of goat meat processed by butchers under local marketing conditions were investigated during 2008-9. Moisture content of goat meat group A was higher (78.30±0.48%) followed by group B (75.70±0.50%) and group C (73.8±0.061%). Protein, fat, ash content in meat of group A was lowered (15.31±0.68, 1.77±0.24 and 1.20±0.06%, respectively) and increase with advance slaughter age (Group B; 18.43±0.80, 2.71±0.18 and 1.31±0.08% and Group C; 20.30±0.91, 3.07±0.17 and 1.63±0.07. The results conclude the meat of goat slaughtered in advanced age may have an extensive advantage to reduce qualitative and quantitative losses of end products and variation in meat of different age groups animal were found.